RADIOACTIVE (TH, U) AND RARE EARTH ELEMENTS IN NATURAL WATERS OF CENTRAL SIKHOTE-ALIN (PRIMORSKY KRAI) - Alena V. Vetoshkina; Igor Yu. Chekryzhov; Аlexander М. Panichev; Еlena А. Vakh; Natalia V. Baranovskaya; Tatyana N. Lutsenko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
Relevance. The complex picture of Th and U balance, their relationship with rare earth elements in natural waters of various compositions and the importance of these elements as indicators for hydrogeochemical constructions and conclusions determines the relevance of their study in different regions using modern analytical methods. Objects: content and balance of uranium and thorium in natural waters of three regions of the central Sikhote-Alin in the Primorsky Krai: «Shanduy», «Vanchin», «Bikin». Methods. 55 elements were detected by inductively coupled plasma mass spectrometry (ICP-MS) (spectrometer Agilent 7700х, Agilent Techn., USA). The second tube was used to determine five macrocations by atomic emission spectrometry (iCAP 7600 Duo spectrometer), as well as six anions by ion chromatography (ion liquid chromatograph LC-20, Shimadzu, Japan). Results. New data are presented on the content of radioactive elements (thorium and uranium), the value of Th/U, the content of rare earth elements in natural waters confined to the location of the kudurs (specific places of manifestation of lithophagy) in three regions geographically located in the central Sikhote-Alin of the Primorsky Krai: «Shanduy», «Vanchin», «Bikin». The average contents of radioactive (Th, U) and rare earth (La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu) elements in natural waters were established. The studied natural waters are ultrafresh and fresh with an average mineralization of 52,4 mg/l. U content in waters ranges from 0,005 to 1,067 μg/l. Th concentration in water varies from 0,003 to 2,299 μg/l. The thorium–uranium ratio in waters varies from 0,01 to 5,3. A positive relationship was found between the content of thorium in the waters and the amount of rare earth elements.